Computational study on the inhibition mechanisms of the ziegler-natta catalyst in the propylene polymerization process: part 1 effects of acetylene and methylacetylene (2024)
Acetylene and methylacetylene are impurities commonly found in the raw materials used for the production of polymers such as polypropylene and polyethylene. Experimental evidence indicates that both acetylene and methylacetylene can decrease the productivity of the Ziegler-Natta catalyst and alter the properties of the resulting polymer. However, there is still a lack of understanding regarding the mechanisms through which these substances affect this process. Therefore, elucidating these mechanisms is crucial to develop effective solutions to this problem. In this study, the inhibition mechanisms of the Ziegler-Natta catalyst by acetylene and methylacetylene are presented and compared with the incorporation of the first propylene monomer (chain initiation) to elucidate experimental effects. The Density Functional Theory (DFT) method was used, along with the B3LYP-D3 functional and the 6-311++G(d,p) basis set. The recorded adsorption energies were −11.10, −13.99, and −0.31 kcal mol−1, while the activation energies were 1.53, 2.83, and 28.36 kcal mol−1 for acetylene, methylacetylene, and propylene, respectively. The determined rate constants were 4.68 × 1011, 5.29 × 1011, and 2.3 × 10−8 M−1 s−1 for acetylene, methylacetylene, and propylene, respectively. Based on these values, it is concluded that inhibition reactions are more feasible than propylene insertion only if an ethylene molecule has not been previously adsorbed, as such an event reinforces propylene adsorption.